On intuitive use, physicality and tangible user interfaces. (12th November 2009) - Israel, Johann H.; Hurtienne, Jorn; Pohlmeyer, Anna E.; Mohs, Carsten; Kindsmuller, Martin; Naumann, Anja
'Intuitive to use' is so often assigned to tangible user interfaces (TUIs) and physical interaction, for example, in conference lectures, informal communication and in scientific publications, that it seems obvious that physicality evokes intuitive use. However, on closer inspection the topic becomes less obvious. It appears that the use of the term intuitive are diverse and a common definition is still missing; this is true in general for the field HCI but it is particularly true for the fields physicality and tangible interaction. This paper provides a definition of intuitive use and reviews formerly separated ideas on physicality, and tangible user interfaces and intuitive use that were partly included in past publications. We also investigate further aspects which enable or facilitate intuitive use, namely image schemas and familiarity. As interaction has an impact on the overall product experience, we also discuss whether intuitive use influences the users' aesthetic judgements of such products.